Human Erysipelothrix rhusiopathiae infection via bath water – case report and genome announcement - Zautner, Andreas E.; Tersteegen, Aljoscha; Schiffner, Conrad-Jakob; Ðilas, Milica; Marquardt, Pauline; Riediger, Matthias; Delker, Anna Maria; Mäde, Dietrich; Kaasch, Achim J. (Frontiers in Cellular and Infection Microbiology, 2022)
Erysipelothrix rhusiopathiae is a facultative anaerobic, environmentally stable, Gram-positive rod that causes swine and avian erysipelas as a zoonotic pathogen. In humans, the main manifestations described are circumscribed erysipeloid, generalized erysipeloid, and endocarditis. Here, we report a 46-year-old female patient who presented to the physician because of redness and marked functio laesa of the hand, in terms of a pain-related restricted range of motion, and was treated surgically. E. rhusopathiae was detected in tissue biopsy. The source of infection was considered to be a pond in which both swine and, later, her dog bathed. The genome of the isolate was completely sequenced and especially the presumptive virulence associated factors as well as the presumptive antimicrobial resistance genes, in particular a predicted homologue to the multiple sugar metabolism regulator (MsmR), several predicted two-component signal transduction systems, three predicted hemolysins, two predicted neuraminidases, three predicted hyaluronate lyases, the surface protective antigen SpaA, a subset of predicted enzymes that potentially confer resistance to reactive oxygen species (ROS), several predicted phospholipases that could play a role in the escape from phagolysosomes into host cell cytoplasm as well as a predicted vancomycin resistance locus (vex23-vncRS) and three predicted MATE efflux transporters were investigated in more detail.